Journal of Intellectual Property Rights: A Bibliometric Study - Garg, K.C.; Anjana, A.K. (DESIDOC Journal of Library & Information Technology, 2014)
This paper analyses 605 papers published in the Journal of Intellectual Property Rights during 1996-2012, which indicates that the inflow of papers has increased during the period of study. This is an attempt to find the popularity of journal among the scientific community as well as policy makers. The study shows that number of references per paper is increasing and the average reference per paper is 23. The proportion of single authored papers is decreasing, while the share of multi-authored papers is on the rise. About one-fourth of the papers published in the journal are from abroad and the rest from India. Among foreign countries US is the largest contributor. Among the performing sectors, academic institutions are the largest contributors to the journal followed by research institutions. As an agency, CSIR has contributed the highest number of papers and several of the prolific institutions and authors are also from CSIR. DESIDOC Journal of Library & Information Technology, 2014, 34(1), pp. 66-73. http://dx.doi.org/10.14429/djlit.34.5948